Corrigendum: Magnetization process of the S = 1/2 Heisenberg antiferromagnet on the floret pentagonal lattice (2021 J. Phys. Commun.5 125008). (1st August 2022) - Furuchi, Rito; Nakano, Hiroki; Todoroki, Norikazu; Sakai, Toru
Abstract: We report an inconsistent way of plotting in a figure in Furuchi R, Nakano H, Todoroki N and Sakai T (2021 J. Phys. Commun. 5 125 008) and present a consistent figure. This replacement does not change the main conclusions in Furuchi R, Nakano H, Todoroki N and Sakai T (2021 J. Phys. Commun. 5 125 008).